Analysis Of The Validity And Reliability Of A Critical Thinking Skills Instrument On The Topic Of Wave-Particle Duality Using Rasch Model - Tarpin Juandi; Ida Kaniawati; Achmad Samsudin; Lala Septem Riza; Susilawati Susilawati; Sapiruddin Sapiruddin (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
This study aims to analyse the validity and reliability of a critical thinking skills instrument on the topic of wave-particle dualism using the Rasch model. Data collection was carried out by administering a critical thinking skills test to students enrolled in a modern physics course. A total of 36 students from a university in West Nusa Tenggara participated. Data analysis was performed using the Rasch model through the Winsteps 4.6.1 software. The results indicated that the instrument is valid and reliable. The instrument's validity was tested by examining the data's fit to the Rasch model through infit and outfit MNSQ values and ZSTD, all of which were within the expected acceptance range. Construct validity was analysed through standardized residual variance, showing that the Rasch model can explain most of the variance in the data. Similarly, the instrument's reliability showed that the item reliability was in the very good category (0.93) and the person reliability was in the moderate category (0.68), with a Cronbach's alpha value of 0.86, indicating very good internal reliability. These findings confirm that the Rasch model is effective in assessing and improving the quality of critical thinking skills evaluation instruments in the context of modern physics education.